THE ROLE OF TRANSLATION IN LEARNING A FOREIGN LANGUAGE - Muminova Dilshodakhon Abduvakhitovna (Лучшие интеллектуальные исследования, 2023)
The role of translation in learning a foreign language, its effectiveness as a language learning method, and its importance in language learning are huge, and the importance of this method in teaching students is widely covered in this article.